MISKAWAYH ON PLEASURE. Issue 2 (31st July 2015) - Adamson, Peter
Abstract This paper provides an analysis and translation of a previously edited, but otherwise unstudied work by Miskawayh (d. 1030) entitled On Pleasures and Pains (Fī al-Laḏḏāt wa-al-ālām). After a brief orientation regarding the Aristotelian account of pleasure in the Nicomachean Ethics, which is Miskawayh's main source, the theory of pleasure set out in On Pleasures and Pains is compared to the discussion of pleasure in Miskawayh's better known Refinement of Character (Tahḏīb al-aḫlāq). Despite considerable harmony between the two texts, their treatments of pleasure differ in that the Refinement accepts, whereas On Pleasures and Pains rejects, the "restoration" theory of pleasure of Plato's Timaeus.